Strategi Badan Pengawas Pemilihan Umum dalam Pencegahan Pelanggaran Politik Uang Pada Pemilu Tahun 2024 di Kabupaten Bogor - Andani, Herli; Pratidina, Ginung (Karimah Tauhid, 2025)
The practice of money politics is an act of violation in elections that is very difficult to eliminate. Bawaslu as a supervisory body is tasked with preventing and following up on violations of these money practices. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation and literature study. The purpose of this research is to find out what strategies are pursued by Bawaslu Bogor Regency in preventing money politics violations. The results of this study are Bawaslu's efforts to prevent money politics in the following ways; a) Conducting socialisation to various parties, especially community organisations that are vulnerable to being involved in money politics. b) Coordinating with government agencies and universities in election supervision. c) Conducting visits and delivering prohibitions on the practice of money politics to political parties. d) Utilising social media to expand the money politics prevention campaign.